Comprehensive Raman study of epitaxial silicene-related phases on Ag(111) - Solonenko, Dmytro; Gordan, Ovidiu D.; Le Lay, Guy; Zahn, Dietrich R. T.; Vogt, Patrick (Beilstein Journal of Nanotechnology, 2017)
The investigation of the vibrational properties of epitaxial silicene and two-dimensional (2D) Si structures on the silver(111) surface aims for a better understanding of the structural differences and of the simplification of the seemingly complex phase diagrams reported over the last years. The spectral signatures of the main silicene phases epitaxially grown on Ag(111) were obtained using in situ Raman spectroscopy. Due to the obvious 2D nature of various epitaxial silicene structures, their fingerprints consist of similar sets of Raman modes. The reduced phase diagram also includes other Si phases, such as amorphous and crystalline silicon, which emerge on the Ag surface at low and high preparation temperatures, respectively. The Raman signatures obtained along with their interpretations provide the referential basis for further studies and for potential applications of epitaxial silicene.
Keywords: epitaxial silicene; in situ Raman spectroscopy; phase diagram